Isolation, Identification, and Investigation of Pathogenic Bacteria From Common Carp (Cyprinus carpio) Naturally Infected With Plesiomonas shigelloides - Chen, Huijie; Zhao, Yuanli; Chen, Kuangxin; Wei, Yulai; Luo, Hongrui; Li, Yongming; Liu, Fei; Zhu, Zuoyan; Hu, Wei; Luo, Daji (Frontiers in Immunology, 2022)
Various bacterial diseases have caused great economic losses to the high-density and intensive aquaculture industry; however, the pathogenic mechanism underlying the large-scale challenged to caused by many bacteria remain unclear, making the prevention and treatment of these diseases difficult. In the present study, we isolated a bacterial strain from Cyprinus carpio having a typical bacterial disease and named it Cc2021. Through subsequent morphological observations, a regression challenge, biochemical identification, and 16S rRNA gene sequence analysis, we determined Cc2021 to be Plesiomonas shigelloides. Subsequently, we comprehensively investigated the pathogenicity of P. shigelloides in C. carpio through a regression challenge and assessed the underlying the pathogenic mechanism. Mortality results revealed that P. shigelloides is highly pathogenic and infects various tissues throughout the body, resulting in edema of the liver, spleen, and body and head kidneys. Histopathological analysis revealed obvious inflammation, bleeding, and necrosis in the intestine, spleen, and head kidney. The body’s immune tissues actively produce complement C3, superoxide dismutase, and lysozyme after a challenge to resist bacterial invasion. With regard to the underlying pathogenesis of P. shigelloides, comparative transcriptome analysis revealed 876 upregulated genes and 828 downregulated genes in the intestine of C. carpio after the challenge. Analysis of differentially expressed unigenes revealed the involvement of major immune pathways, particularly the TNF signaling pathway, interleukin (IL)-17 signaling pathway, and Toll-like receptor signaling pathway. The present study provides new valuable information on the immune system and defense mechanisms of P. shigelloides.